Smith–Purcell radiation amplifier. (14th October 2015) - Oganesyan, Koryun B
Abstract: In the framework of the earlier derived dispersion equation, we study induced Smith–Purcell (SP) radiation of relativistic electron beam in the absence of a resonator. We offer a new method for calculation of coefficients for partial amplitudes in the case of rectangular grating. Using this method, as an important example of applications of our earlier derived results (Klochkov D N, Artemyev A I, Oganesyan K B, Rostovtsev Y V and Hu C K 2010 J. Mod. Opt . 57 2060–8 ), we calculate the growth rate of the SPFEL with a rectangular grating. The growth rate dependences on harmonic number, observation angle and relativistic factor are presented.